Care networks in play: Understanding death of a parent as a contributing factor to homelessness. Issue 7 (3rd October 2017) - Perry, Tam E.; Hassevoort, Luke; Petrusak, Justin
ABSTRACT: Offering an understanding of specialized service needs of those becoming homeless because of the death of a parent or parental figure, this project is set in Detroit's urban context, where residents face economic hardship and intergenerational poverty. In this study, we analyze the voices of practitioners ( n = 5) and men ( n = 5) who have experienced parental death as a contributing factor to homelessness in Detroit, Michigan. Findings include the following: (1) the impact of death and dying experiences on these men and (2) the role of care networks in these men's lives, particularly when these men have and lack "default" caregivers after death of a parent. This community-based research project was a result of a partnership between a local agency serving persons experiencing homelessness, where the practitioner initiated the project with the researcher. The paper concludes with implications for social work practice.